Comparison Analysis of Breadth First Search and Depth Limited Search Algorithms in Sudoku Game - Tirsa Ninia Lina; Matheus Supriyanto Rumetna (Indonesian Scientific Journal, 2021)
Sudoku is a game that sharpens the brain and is very well known. But the problem faced in this condition is how we can find a solution for the completion of this game. Problems with the Sudoku game can be solved by using the concept of Artificial Intelligence (AI). Some of the algorithms that can be used are the Breadth First Search (BFS) and Depth Limited Search (DLS) algorithms. The purpose of this research is to find a solution for Sudoku and make a comparative analysis of the search results of the two algorithms. The results obtained are application design in the form of a simulation of the completion of the Sudoku game problem with two algorithms. And it has been proven from the two algorithms that DLS is more efficient and faster than BFS. While BFS itself has advantages, in terms of a more structured and systematic search system that is able to find all possible numbers in each box. In this case, if a Sudoku question has more than one answer, then BFS will find it.